Microstructure evolution and recrystallization analysis of hot rolled NM360/Q345R composites. (4th July 2018) - Zhao, Guanghui; Ma, Lifeng; Huang, Qingxue; Li, Juan; Zhi, Chenchen; Cheng, Muhua
Abstract: In this paper, the effects of rolling reduction rates on the microstructure of the NM360/Q345R composite were studied. With the electron backscatter diffraction(EBSD) contribution, the microstructure evolution and recrystallization of the bonded interface were mainly analyzed at various reduction rates (30%, 50%, 70% and 80%). With the rolling reduction rate increased, the grains of the NM360 and the Q345R became low-sized and denser. With the reduction rate increase up to 80%, the grains of NM360 and Q345R formed the same low-sized equiaxed grains, whereas the two materials achieved a coordinated deformation. A continuous dynamic recrystallization mechanism existed in the NM360/Q345R composites. A high number of low-sized grains in the NM360/Q345R bonded interface existed, which were basically the recrystallized blue region and the deformed red region. Moreover, with the reduction rate increase up to 80%, the recrystallization of the NM360 was significantly difficult compared to the Q345R. Also, a high number of red high density deformation zones were formed in the NM360.